2008
DOI: 10.1021/ie071274z
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carboxyl Content on the Characteristics of TMP Long Fibers

Abstract: This work examined the effects of carboxyl content on the characteristics of TMP long fibers. The carboxyl groups on TMP long fibers were generated by a TEMPO-mediated oxidation using different amounts of sodium hypochlorite. In general, the increases in carboxyl content improved the tensile and burst indices but reduced the tear index and fines retention. It was also found that low carboxyl content on oxidized long fibers could adsorb part of the dissoluble substance (DS) and other substances, reducing the DS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 14 publications
1
15
0
Order By: Relevance
“…As cellulose microfibrils are tightly embedded in lignin and hemicellulose matrixes, 26,27 isolation of pure cellulose requires intensive chemical and energy input. Therefore, CNCs and cellulose nanofibrils (CNFs) have also been isolated from less purified lignocellulosics, such as mechanically defibrillated wood pulp containing varying amounts of lignin and hemicellulose, 28−30 hemp fibers, 31,32 softwood thermomechanical pulp, 33,34 and hardwood kraft pulp, 35 as well as holocellulose from softwood, hardwood and rice straw, 36 bagasse pulp, 37 and coconut fibers. 38 While in 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) mediated oxidation most hemicellulose in softwood, hardwood, and herbaceous holocellulose, 32,36 as well as lignin in hemp fibers 31 and softwood thermomechanical pulp 33,34 were degraded to become water-soluble and removed, sulfuric acid hydrolysis of bagasse pulp containing 27% hemicellulose 37 and partially delignified coconut fibers 38 has shown to leave some noncellulosics with CNCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…As cellulose microfibrils are tightly embedded in lignin and hemicellulose matrixes, 26,27 isolation of pure cellulose requires intensive chemical and energy input. Therefore, CNCs and cellulose nanofibrils (CNFs) have also been isolated from less purified lignocellulosics, such as mechanically defibrillated wood pulp containing varying amounts of lignin and hemicellulose, 28−30 hemp fibers, 31,32 softwood thermomechanical pulp, 33,34 and hardwood kraft pulp, 35 as well as holocellulose from softwood, hardwood and rice straw, 36 bagasse pulp, 37 and coconut fibers. 38 While in 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) mediated oxidation most hemicellulose in softwood, hardwood, and herbaceous holocellulose, 32,36 as well as lignin in hemp fibers 31 and softwood thermomechanical pulp 33,34 were degraded to become water-soluble and removed, sulfuric acid hydrolysis of bagasse pulp containing 27% hemicellulose 37 and partially delignified coconut fibers 38 has shown to leave some noncellulosics with CNCs.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In Leroux et al's work, the dosages of the sodium hypochlorite were varied from 1.25% (% v/v, approximately 9.24 mmol/g) to 8.3% (% v/v, approximately 61.4 mmol/g), and the yield was not given. However, a large drop in yield occurred when the dosage of sodium hypochlorite was 6.0 mmol/(g of fiber) or higher (Mao et al 2008;Okita et al 2009). Figure 2 shows the association between the NaClO (%) additions and the carboxylate content of the treated pulps, as well as the tensile index of the handsheets.…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…The recovery ratio of deinked pulps pretreated with the TEMPO system at the highest amount of NaClO (sample 7, 83.5%) decreased by approximately 1.8% in contrast to the pulp treated with hydrogen peroxide alone (sample 2, 85.3%). The loss may be attributed to the lignin, hemicelluloses, and a part of cellulose, which were removed as water-soluble compounds (Mao et al 2008). Besides, some material from the deinked fibers might be degraded into soluble molecules (e.g., monosaccharides) during the oxidation by the TEMPO system, and these products may be lost during the washing process (Saito and Isogai 2003;Saito et al 2006).…”
Section: Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…Some recent studies (Leroux et al 2006;Dang et al 2007;Law et al 2007;Leroux et al 2007;Mao et al 2008;Gomes et al 2009) have revealed that carboxylic acid groups introduced on fiber surface by TEMPO-mediated oxidation can enhance the inter-fiber interaction by hydrogen bonding. The inter-fiber bonding-dependent factors, tensile and burst indexes, increased significantly after TEMPO-mediated oxidation for both kraft pulp (Saito and Isogai 2006) and TMP (Leroux et al 2006;Law et al 2007;Mao et al 2008).…”
Section: Strength Propertiesmentioning
confidence: 99%
“…TEMPO (2,2,6,6-tetramethylpiperidyl-1-oxyl)-mediated oxidation, which was first used for polysaccharide oxidation in 1995 (De Nooy et al 1995), is considered a very effective method for paper strength enhancement because of the introduction of the carboxyl and aldehyde groups on fiber surface (De Nooy et al 1995;Saito and Isogai 2006). TEMPO-mediated oxidation had been used for kraft pulp enhancement by Dang et al (2007), and for thermomechanical pulp (TMP) enhancement by Law and Mao (Law et al 2007;Mao et al 2008); it was also used for deinking pulp modification by Leroux et al (2007). All the results indicated that TEMPO-mediated oxidation could improve the paper strength remarkably.…”
Section: Introductionmentioning
confidence: 99%